Maturity Process Of Jim Hawkins In R.L Stevenson's Treasure Island: Behavioristic Approach - Suryani, Puji (2004)
The study is about the relation between environment and maturity process in R.L Stevenson's Treasure Lsland The Objectives Of Study are to analyze R.L Stevenson's Treasure Lsland based on the structural elements and the behavior of the major characters based on the psychological approach especially behavioristic. In analyzing Treasure Lsland., the writer moves uses of the behavioristic perspective, and qualitative method the object of the research is the personality of the major character and behavior derived from R.L Stevenson's novel that is published in 1882 by Thomas Nelson and sons Ltd. The data sources are using literary data that are divided into two categories, primary data is the novel of Treasure Lsland it self and the secondary one includes several reference books of psychology, literary theory books, and other relevant information from the web-site The method of the data collection of the research is documentation, and the primary data in short document used as exidence. The techniques of data are descriptive and content analysis. The outcome of this study shows that the environment as the external factor provides an experience that turned out to be maturity inducing. The maturity of the major character occurs because of he gives response toward the experiences and adjusting his behavior to survive his life.